The Effectiveness of a Cognitive Behavior Training Program in Reducing Psychological Stress among Mother’s of Children with Spina Bifida - Gaith, Suad; Masri, Anas; Mizaguabian, Annie (Jordan Journal of Educational Sciences, 2011)
The study aimed at investigating the effectiveness of a training program based on Cognitive–Behavior Theory to reduce the level of psychological stress among a sample of mothers of Spina Bifida children, intentionally chosen from Al-Hussein Society for Habilitation and Rehabilitation of the Physically Challenged. The subjects of this study were assigned randomly to two groups: an experimental group which consisted of (15) mothers who received the training program and a control group which consisted of (15) mothers who did not receive the training program. The psychological stress scale was applied on both groups; before and after the program afollowing test a month later. To test the two null hypothoses of the study means, standard deviations, and ANCOVA were computed The results revealed significant differences at (α ≤ .05) between the means of the two groups (experimental and control) of the total score of psychological stress scale used at the post-test and one-month follow up, which indicated the effectiveness of the training program in reducing the level of psychological stress among participants and its continued effect . In addition results of MANOVA revealed significant differences between the two groups of the study on some sub-scales of psychological stress scale in post- and follow –up tests